Stellar-to-halo mass relation of cluster galaxies. Issue 1 (4th July 2017) - Niemiec, Anna; Jullo, Eric; Limousin, Marceau; Giocoli, Carlo; Erben, Thomas; Hildebrant, Hendrik; Kneib, Jean-Paul; Leauthaud, Alexie; Makler, Martin; Moraes, Bruno; Pereira, Maria E. S.; Shan, Huanyuan; et al.
Abstract: In the formation of galaxy groups and clusters, the dark matter haloes containing satellite galaxies are expected to be tidally stripped in gravitational interactions with the host. We use galaxy–galaxy weak lensing to measure the average mass of dark matter haloes of satellite galaxies as a function of projected distance to the centre of the host, since stripping is expected to be greater for satellites closer to the centre of the cluster. We further classify the satellites according to their stellar mass: Assuming that the stellar component of the galaxy is less disrupted by tidal stripping, stellar mass can be used as a proxy of the infall mass. We study the stellar-to-halo mass relation of satellites as a function of the cluster-centric distance to measure tidal stripping. We use the shear catalogues of the Dark Energy Survey (DES) science verification archive, the Canada–France–Hawaii Lensing Survey (CFHTLenS) and the CFHT Stripe 82 surveys, and we select satellites from the redMaPPer catalogue of clusters. For galaxies located in the outskirts of clusters, we find a stellar-to- halo mass relation in good agreement with the theoretical expectations from Moster et al. for central galaxies. In the centre of the cluster, we find that this relation is shifted to smaller halo mass for a given stellar mass. We interpret this finding as further evidence for tidal stripping of dark matter haloes in high-density environments.